Micro-elimination of Hepatitis C Virus Infection in Thalassemic Patients - Tampaki, Maria; Kountouras, Dimitrios; Delicou, Sophia; Xidaki, Aikaterini; Kiriakopoulou, Dimitra; Fragkodimitri, Christina; Limvaios, Ioannis; Drosou, Marouso; Vini, Dimitra; Petropoulou, F; Kattamis, Antonios; Koskinas, John (British Journal of Healthcare and Medical Research, 2024)
Background and objectives: We aimed to deploy an intra-hospital Hepatitis C Virus (HCV) micro-elimination project for thalassemic patients in collaboration with 2 pediatric departments and 4 transfusion units. This initiative took place between 2013-2022 and included various HCV regimens according to existing treatments and reimbursement criteria per period. Methods: HCV screening was performed at the Transfusion units and Pediatric departments. Following HCV diagnosis, thalassemic patients were referred to our Hepatology department for HCV-RNA and genotype examination, evaluation of liver fibrosis and finally to administer treatment. Results: In total, 119 patients were treated with direct-acting anti-viral agents (DAAs) in our center. SVR was achieved in 110/119 (92.4%) with the first line DAAs available. The SVR rates were not significantly associated with treatment experience, the presence of cirrhosis or liver iron concentration values. Treatment was generally well tolerated, and no significant interactions were recorded between DAAs and chelation agents or other co-medications. All patients who failed in the 1st line DAAs received 2nd line treatment and achieved SVR. Conclusions: Close collaboration between hematologists and hepatologists facilitates HCV diagnosis and access to effective and safe treatments for thalassemic patients. Micro-elimination projects for this population should be a priority on the road to Global HCV elimination.